Rectal epithelial cell mitosis and expression of macrophage migration inhibitory factor are increased 3 years after Roux-en-Y gastric bypass (RYGB) for morbid obesity: implications for long-term neoplastic risk following RYGB. Issue 7 (8th February 2011) - Kant, Prashant; Sainsbury, Anita; Reed, Karen R; Pollard, Stephen G; Scott, Nigel; Clarke, Alan R; Coletta, P Louise; Hull, Mark A
Abstract : Background: Rectal epithelial cell mitosis and crypt size, as well as expression of proinflammatory genes including macrophage migration inhibitory factor ( MIF ), are increased 6 months after Roux-en-Y gastric bypass (RYGB) in morbidly obese patients. Tests were carried out to determine whether these putative colorectal cancer risk biomarkers remained elevated long term after RYGB, and the mechanistic basis, as well as the functional consequences, of Mif upregulation in intestinal epithelial cells was investigated. Methods: Rectal mucosa and blood were obtained a median of 3 years after RYGB from the original cohort of patients with RYGB (n=19) for crypt microdissection, real-time PCR, immunohistochemistry for MIF and immunoassay of proinflammatory markers. Immunohistochemistry for Mif and bromodeoxyuridine labelling were performed on AhCre + mouse and Apc Min/+ mouse (with and without functional Mif alleles) intestine, respectively. Results: Rectal epithelial cell mitosis and crypt size remained elevated 3 years after RYGB compared with preoperative values (1.7- and 1.5-fold, respectively; p<0.05). There was a 40-fold (95% CI 13 to 125) increase in mucosal MIF transcript levels at 3 years associated with increased epithelial cell MIF protein levels. Conditional Apc loss in AhCre + mice led to increased epithelial cell Mif content. Mif deficiency in Apc Min/+ mice was associated with a combined defect in intestinal epithelial cell proliferation and migration, which was reflected by the longitudinal clinical data. Conclusions: Mucosal abnormalities persist 3 years after RYGB and include elevation of the protumorigenic cytokine MIF, which is upregulated following Apc loss and which contributes to intestinal epithelial cell homeostasis. These observations should prompt clinical studies of colorectal neoplastic risk after RYGB.